The Reciprocal Relationships Between Escalation, Anger, and Confidence in Investment Decisions Over Time - Jackson, Alexander T.; Howes, Satoris S.; Kausel, Edgar E.; Young, Michael E.; Loftis, Megan E. (Frontiers in Psychology, 2018)
Research on escalation of commitment has predominantly been studied in the context of a single decision without consideration for the psychological consequences of escalating. This study sought to examine (a) the extent to which people escalate their commitment to a failing course of action in a sequential decision-making task, (b) confidence and anger as psychological consequences of escalation of commitment, and (c) the reciprocal relationship between escalation of commitment and confidence and anger. Participants were 110 undergraduate students who completed a series of investment decisions regarding a failing endeavor. Results revealed that although a high proportion of individuals escalate through all decisions, the extent to which they escalated decreased with each decision as they were less willing to invest money in the project. Furthermore, as participants escalated, confidence in one’s decision decreased and anger increased. Lastly, the analyses revealed that the relationship between escalation and confidence is reciprocal. Escalation was negatively associated with confidence, and confidence predicted escalation in the subsequent decision. These results highlight the importance of considering both the determinants and psychological consequences of escalation of commitment.